2009
DOI: 10.1103/physreve.80.031915
|View full text |Cite
|
Sign up to set email alerts
|

DNA stretching and multivalent-cation-induced condensation

Abstract: Motivated by measurements on stretched double-stranded DNA in the presence of multivalent cations, we develop a statistical mechanical model for the compaction of an insoluble semiflexible polymer under tension. Using a mean-field approach, we determine the order of the extended-to-compact transition and provide an interpretation for the magnitude and interval of tensions over which compaction takes place. In the simplest thermodynamic limit of an infinitely long homogeneous polymer, compaction is a first-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In our one-dimensional continuum description of the DNA molecule, we account for DNA elasticity, DNA-DNA interactions, fluctuations, and configurational entropy in the tails, helices, and toroidal loops. For the description of the toroidal structures, we have added the twist effects to a well-established model (22,23). And for the description of the supercoiled structures, we follow the treatment in Argudo and Purohit (11) including the effects of multivalent cations in the internal energy.…”
Section: Introductionmentioning
confidence: 99%
“…In our one-dimensional continuum description of the DNA molecule, we account for DNA elasticity, DNA-DNA interactions, fluctuations, and configurational entropy in the tails, helices, and toroidal loops. For the description of the toroidal structures, we have added the twist effects to a well-established model (22,23). And for the description of the supercoiled structures, we follow the treatment in Argudo and Purohit (11) including the effects of multivalent cations in the internal energy.…”
Section: Introductionmentioning
confidence: 99%
“…Following Refs. [23,24] we estimate the free energy of the WLC at a given value of the extending external force f = ql p E s , where q is the effective linear charge density. A similar approach has been developed initially for the end forces.…”
Section: B the Free Energy Change Due To Wlc Stretchingmentioning
confidence: 99%
“…We investigate the conditions affecting the orientational order formation of short double-strand DNA fragments, immersed in the flexible polymer. It is shown that short double-strand DNA fragments exhibit the formation of a liquid crystalline ordered phase, in dependence on the value of the Flory-Huggins parameter, aspect ratio , and the attraction energy (Mamasakhlisov et al, 2009;Todd et al, 2008) Metropolis Monte Carlo method based on the extended cluster approach (Danilov, Dailidonis, van Mourik, & Fruchtl, 2011a, 2011bDailidonis, Danilov, Früchtl, & van Mourik, 2011) is used to investigate adenine-adenine (AA), guanine-guanine (GG), thymine-thymine (TT), and cytosine-cytosine (CC) homoassociates in a cluster consisting of 400 water molecules. The starting structures taken were AA N(7) amino symmetric, TT N (3) -O(4) symmetric, GG N(1) -O(6) symmetric, and CC N(3) amino symmetric base pairs.…”
mentioning
confidence: 99%